The Brussels International Development Plan (IDP) - Jean-Michel Decroly; Mathieu Van Criekingen (Brussels Studies, 2009)
The adoption of an International Development Plan (IDP) by the regional government at the end of 2007 marks a significant transition in urban policies in Brussels. This text seeks to highlight the essential options of the IDP and presents a critical analysis of it. In our view, the IDP indicates essentially the formalisation of a relatively new strategy in Brussels, aimed at the development of significant portions of the regional territory for the purposes of private real estate developments of a speculative character which are supposed to function as new levers in urban “revitalisation”. As such, the Brussels IDP is in keeping with a serious tendency towards the widespread use of urban policies of neoliberal inspiration, which encourage the rehabilitation of city centres without taking into account the effects they have on intensifying the city’s social and spatial divisions.